Biochemical and populational responses of an aquatic bioindicator species, Daphnia longispina, to a commercial formulation of a herbicide (Primextra® Gold TZ) and its active ingredient (S-metolachlor). (June 2015) - Neves, M.; Castro, B.B.; Vidal, T.; Vieira, R.; Marques, J.C.; Coutinho, J.A.P.; Gonçalves, F.; Gonçalves, A.M.M.
Highlights: The toxicity and multi-generational effects of the commercial formulation and its active ingredient (a.i.) were assessed. Commercial formulation and the a.i. caused a significant effect on the life history parameters of D. longispina . The commercial formulation (Primextra® Gold TZ) is more toxic than the a.i. (S-metolachlor) isolated. The percentage of FA was higher in neonates and mothers exposed to the a.i. than those not exposed to the toxicant. A full recovery of the cladoceran populations in the absence of the toxicant is expected after a post-exposure. Abstract: The growing demand of human populations for food supplies has led to an increase in the use of synthetic products, mainly pesticides, which induce adverse effects not only to target organisms, but also to non-target biota of agroecosystems. Aquatic ecosystems in the proximity of agricultural areas are particularly vulnerable to pesticides, which cause underperformance or extinction of non-target sensitive species. Once in the aquatic system, these chemicals can affect biological processes at multiple levels (molecular, individual, populational), causing ecosystem imbalance across multiple scales. In this study, the effect of a commercial formulation of a herbicide (Primextra® Gold TZ) and its main active ingredient (a.i., S -metolachlor) was studied on a freshwater cladoceran species ( Daphnia longispina ), at different levels of biological organization and temporal scales. S -metolachlor is used in many herbicide formulations applied in corn/maize cultures, which is a relevant culture worldwide. As a first step, the acute and chronic effects of both commercial formulation and a.i. were quantified, and both formulations negatively affected the cladoceran's survival and reproductive parameters (age at first reproduction, number of offspring and number of broods), as well as the population's rate of increase. Whilst acute effects were comparable, the commercial formulation was slightly more toxic (EC50 was two-times lower) than the a.i. in chronic exposures, being prejudicial to D. longispina populations above 4.0 mg/L of S -metolachlor. In a second experimental step, we focused on the potential multi-generational impacts of the exposure to the a.i. alone on biochemical (lipid biomarkers, namely fatty acids) and populational responses, because of the relevance of S -metolachlor as a biosynthesis inhibitor in many herbicidal formulations. The herbicide caused a significant decrease in Daphnia fecundity (in the size of the 1st clutch), but no concomitant alterations were found in fatty acid profiles of mothers or offspring. More important, this experiment showed that S -metolachlor did not cause effects in the subsequent generation, thus suggesting that biotic communities may recover after exposure to the xenobiotic.